Avifauna of Son Tra peninsula: recent ornithological surveys with notable migratory bird records - Duy Le; Dang Vo; Ky Hong Thai; Tuan Van Bui; Minh Tai Pham; Van Minh Vo; Chi Cuong-Doan; Luc Van Nguyen; Duc Minh Hoang (Tạp chí Khoa học và Công nghệ)
The Son Tra Peninsula supports a rich avifauna, particularly migratory birds. However, few in-depth studies have been conducted in the area. Between 2016 and 2018, a series of ornithological surveys were conducted across 14 sites using playback, mist-netting, and opportunistic observations along existing roads and transects. A total of 215 bird species were recorded, including 131 resident species, 11 passage migrants, 64 winter visitors, four vagrants, and five breeding visitors. Notably, 105 species were new records for the peninsula, raising the up-to-date checklist of birds to 256 species. The surveys also provided updated data on five globally threatened species and three species with recently extended ranges in Central Vietnam, along with notes on unconfirmed birds and occurrences. There was no robust evidence for the existence of Germain's Peacock-Pheasant (Polyplectron germaini), which was last recorded two decades ago without specific locality information.